An Open STEP-NC Controller Via LabVIEW platform - Minhat, Mohamad (2014)
In future technology in the field of advanced manufacturing, an open architecture controller in CNC system is studied. In this paper, the LabVIEW software platform is chosen and software realization methodology for the CNC system is determined for this application. This research project aims to meet the requirement of open architecture to create a CNC system based on new ISO standards of ISO 14649 and ISO 10303. As a result, open 3-Axis Mill CNC system controller based on component software reuse technology successfully developed. Two case studies of ISO 14649 (example 1 and example 2) were carried out through this developed system.